Answer:
The remainder is 10
Explanation:
The find the remainder when f(x) divided by g(x), find the value of x when g(x) = 0, then substitute it in f to find the value of the remainder
∵ f(x) = 3
+ 2
+ 5
∵ f(x) is divided by x - 1
∴ g(x) = x - 1
→ Equate g(x) by 0 to find x
∵ g(x) = 0
∴ x - 1 = 0
→ Add 1 to both sides
∵ x - 1 + 1 = 0 + 1
∴ x = 1
→ Substitute x in f by 1
∵ f(1) = 3
+ 2
+ 5
∴ f(1) = 3(1) + 2(1) + 5
∴ f(1) = 3 + 2 + 5
∴ f(1) = 10
∵ The remainder is the value of f(1)
∴ The remainder is 10